Pemetaan Terumbu Karang Menggunakan Unmanned Aerial Vehicle (UAV) Di Selatan Pulau Tikus Kota Bengkulu - Denmas Pandu Pamungkas; Dede Hartono; Ari Anggoro (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2022)
ABSTRACTRemote sensing can be interpreted as a technology to obtain information on an object on the earth's surface without direct contact with the object to be studied. Along with the development of current technology, the creation of unmanned aircraft technology or UAV (Unmanned Aerial Vehicle). This research was conducted in June 2020 in the southern waters of Tikus Island. The results of mapping coral reefs in the South of Tikus Island using the UAV (Unmanned Aerial Vehicle) obtained an area of 58.22 ha of Tikus Island South and got four classes, namely the living coral area of 15.34 ha. , Dead Coral and Algae 15.60 ha, Sand 8.08 ha, and Rubble 19.20 ha. Accuracy gets a value of 83.3% and this becomes the accuracy of image data with high resolution.Keywords: UAV, Mapping, Coral reefs, Aerial photography, Tikus Island.ABSTRAKPenginderaan jauh dapat diartikan sebagai teknologi untuk memperoleh informasi suatu objek di permukaan bumi tanpa kontak langsung ke objek yang akan dikaji. Seiring berkembangnya teknologi saat ini terciptanya teknologi pesawat tanpa awak atau UAV (Unmanned Aerial Vehicle). Penelitian ini dilakukan pada bulan Juni 2020 di Perairan Selatan Pulau Tikus, Hasil pemetaan terumbu karang di Selatan Pulau Tikus Menggunakan UAV (Unmanned Aerial Vehicle) mendapatkan Luasan Area Selatan Pulau Tikus 58,22 ha dan mendapatkan empat kelas yaitu luasan Karang hidup 15,34 ha, Karang Mati dan Algae 15,60 ha, Pasir 8,08 ha, dan Rubble 19,20 ha. Akurasi mendapatkan nilai 83.3% dan ini menjadi akurasi data citra dengan resolusi tinggi.Kata Kunci: UAV, Pemetaan, Terumbu karang, Foto udara, Pulau Tikus.